Mexican philosophy for the 21st Century Relajo, Zozobra, and other frameworks for understanding Our World - Sánchez, Carlos Alberto 1975- (Bloomsbury introductions to world philosophies, 2023)
"A sustained reflection on distinctly Mexican concepts that reveals the value of applying Mexican thought to everyday life"-- Provided by publisher.